Factors associated with Adherence to Insulin Self-Administration among Children and Adolescents with Type 1 DM in Iraq - jabbar, Ruqayah Kareem; Mohammed Yawz Jammal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract Adolescents and children with type 1 diabetes have been reported to have challenges regarding adherence to treatment regimens compared with other age groups with diabetes. The study aimed to determine the level of commitment and investigate the effects of different factors on insulin adherence in type 1 diabetes patients in Iraq. This cross-sectional study included face-to-face interview questionnaires with caregivers of children and adolescents. Interviews were conducted in the Specialized Center of Endocrinology and Diabetes in Nasiriyah City, Iraq, from October 4, 2022, to March 30, 2023. The adherence questionnaire consisted of two sections; each consisted of five questions, including insulin and blood glucose recommendations. Blood samples were obtained from the patient to determine fasting blood glucose (FBG) and glycated hemoglobin (HBA1c)—results: 180 patients (86 males and 94 females) with type 1 DM. The mean age, weight, and disease duration were 10.75 (4.36) years, 36.30 (16.41) kg, and 6.24 (3.70) years, respectively. They had uncontrolled blood glucose (208.42 95.0 mg/dl) and HBA1c (9.90 2.85%). The patients (52.2%) were girls with primary school qualifications (43.3%). Most of the caregivers (parents and guardians) were either illiterate (30.6%) or had completed primary school (33.9%). In addition, the patient’s families (43.9%) had low income (0.5 million ID cards). Therefore, most patients (60%) did not visit a doctor regularly or check their blood glucose. Adherence in the studied population could be higher. Focusing on raising their patients’ awareness is pivotal to enhancing their medication adherence to reduce their short- and long-term diabetic complications, improve blood glucose control, and improve clinical outcomes. Keywords: Diabetes, Adherence, Insulin self-medication, Iraqi patients.